Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.33899/edusj.2018.159319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser radiation on the immune response of mice against infection with secondary hydatid disease.I. Growth and development of hydatid cysts.

Abstract: The present study investigated the effect of the Nd-TAG Laser radiation 1000 mw on the viability of the protoscolices of Echinococcus granulosus in vitro, for different durations 40,60,120 and 240 minutes, and on the immune response in BALB/c mice against infection with secondary hydatid disease by injecting the mice with protoscoleces of Echinococus granulosus treated with laser radiation, 70%,57%,50% and 40% viability, compared with the control group of (mice injected with untreated protoscolices with the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many techniques were used against infestation with hydatid disease in experiential animals, such as irradiation with laser, direct electrical current, probiotics and ultrasound (31)(32)(33)(34)(35)(36)(37), all techniques revealed considerable influence to the disease. All the techniques exhibited valuable efficiency against protoscoleces in vitro and cystic echinococcosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques were used against infestation with hydatid disease in experiential animals, such as irradiation with laser, direct electrical current, probiotics and ultrasound (31)(32)(33)(34)(35)(36)(37), all techniques revealed considerable influence to the disease. All the techniques exhibited valuable efficiency against protoscoleces in vitro and cystic echinococcosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Yassen (22), Ali and Salim (23) were used protoscoleces of Echinococcus granulosus exposed to electric current, and they found significant differences between treated and nontreated mice. Furthermore, Ali and Mohammed (24) tested the effect of Laser radiation on the cellular immunity in mice infected with hydatidosis, and found that the laser radiation boosted delayed-type hypersensitivity in treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Six groups of mice were used, five for each group, animals of the 1st, 2nd, 3rd and 4th groups were injected intraperitoneally with 2000 protoscoleces exposed to laser radiation, with viability 70%, 57%, 50%, 40%, the fifth positive control group was injected intraperitoneally with unexposed protoscoleces with 100% viability (15). The sixth negative control group was neither injected with protoscoleces nor exposed to laser radiation.…”
Section: Treatment Schedulementioning
confidence: 99%
“…Researchers investigated better therapeutic non-invasive alternatives, as safe killers for the protoscoleces and stimulative of the immune system, including electromagnetic radiation techniques, ultrasound, ultraviolet, Gamma ray, laser (11)(12)(13)(14)(15)(16)(17)(18), electrical current and nanoparticles (19,20).…”
mentioning
confidence: 99%